Managerial overconfidence, government intervention and corporate financing decision - Ting I.W.K.; Lean H.H.; Kweh Q.L.; Azizan N.A. (Emerald Group Publishing Ltd., 2023)
Purpose The purpose of this paper is to investigate the impact of managerial overconfidence on corporate financing decision and the moderating effect of government ownership on the relationship between managerial overconfidence and corporate financing decision. Design/methodology/approach Pooled OLS, fixed effect models (FEM), and Tobit regressions are employed to examine the relationship between managerial overconfidence, government ownership and corporate financing decision of publicly listed companies in Malaysia for the period of 2002-2011. Findings The authors conclude that: first, CEO overconfidence is significantly and negatively related to corporate financing decision; second, a higher degree of managerial overconfidence would result in lower leverage in GLCs, whereas the effect does not significantly exist in NGLCs; third, a larger ownership of government in a firm will reduce the negative effect of managerial overconfidence on corporate financing decision; fourth, the moderating effect of government ownership on the association between managerial overconfidence and corporate financing decision in GLCs is more effective than NGLCs; and fifth, government intervention plays its role as moderating effect on the relationship between managerial overconfidence and corporate financing decision in firms with lower ownership concentration but not in firms with high ownership concentration (more or equal than 50 percent). Practical implications The finding implies that the moderating effect of government ownership on the association between managerial overconfidence and corporate financing decision in GLCs is more effective than NGLCs. Originality/value The authors make the first attempt to test the moderating effect of government ownership on the relationship between ownership concentration and corporate financing decision. 2016, Emerald Group Publishing Limited.